2001
DOI: 10.1038/35082500
|View full text |Cite
|
Sign up to set email alerts
|

Specific protection against breast cancers by cyclin D1 ablation

Abstract: Breast cancer is the most common malignancy among women. Most of these cancers overexpress cyclin D1, a component of the core cell-cycle machinery. We previously generated mice lacking cyclin D1 using gene targeting. Here we report that these cyclin D1-deficient mice are resistant to breast cancers induced by the neu and ras oncogenes. However, animals lacking cyclin D1 remain fully sensitive to other oncogenic pathways of the mammary epithelium, such as those driven by c-myc or Wnt-1. Our analyses revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
703
5
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 869 publications
(751 citation statements)
references
References 27 publications
38
703
5
5
Order By: Relevance
“…Absence of cyclin D1 in normal MECs results in normal ductal development suggesting that cyclin D1 is dispensable for proliferation of normal MECs. In contrast, cancerous MECs overexpressing ras and neu oncogenes are absolutely dependent on cyclin D1 for malignant transformation (Yu et al, 2001). Similarly, in our study, absence of cyclin D1 in abnormal ERa-overexpressing MECs interrupted cell proliferation and led to apoptosis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Absence of cyclin D1 in normal MECs results in normal ductal development suggesting that cyclin D1 is dispensable for proliferation of normal MECs. In contrast, cancerous MECs overexpressing ras and neu oncogenes are absolutely dependent on cyclin D1 for malignant transformation (Yu et al, 2001). Similarly, in our study, absence of cyclin D1 in abnormal ERa-overexpressing MECs interrupted cell proliferation and led to apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…Cyclin D1 knockout mice undergo normal pubertal mammary gland development but they fail to develop lobuloalveolar structures during pregnancy (Fantl et al, 1995;Sicinski et al, 1995). Cyclin D1 appears to play a very specific role in mammary gland development since the lobuloalveolar defect in cyclin D1 knockout mice occurs even in the presence of cyclin D2 and D3 overexpression (Yu et al, 2001). Genetic replacement of cyclin D1 by cyclin D2 can drive nearly normal mammary gland development even during pregnancy (Carthon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…33 Moreover, CCND1 deficient mice are resistant to breast cancer induced by ERBB2 and RAS oncogenes. 34 These findings point to a central role of CCND1 in breast cancer pathogenesis and our results suggest that this is true also for MBC.…”
Section: Discussionsupporting
confidence: 74%
“…52 Moreover, it has been shown recently that cyclin D1 may be the target of c-erb-B2-and Ras-mediated oncogenic pathways. 53 Of note, recent molecular studies suggest that p27 and other CDK inhibitors of Cip/Kip family, in contrast with their inhibitory function for cyclin E-and cyclin A-dependent CDKs, also may act as positive regulators of cyclin D-dependent kinases (reviewed in Sherr and Roberts 54 ). Indeed, it has been shown that cyclin D3-CDK6-p27 and cyclin D1/2-CDK4/6-p27 complexes are enzymatically active.…”
Section: Discussionmentioning
confidence: 99%